2001
DOI: 10.1097/00006123-200112000-00010
|View full text |Cite
|
Sign up to set email alerts
|

Asymptomatic versus Symptomatic Infarcts from Vasospasm in Patients with Subarachnoid Hemorrhage: Serial Magnetic Resonance Imaging

Abstract: Analysis of the data confirmed the occurrence of asymptomatic infarcts due to vasospasm. These infarcts often developed in noneloquent areas representing perforator territory. MRI investigation of vasospastic lesions referable to intraparenchymal vessels such as perforators complements the study of extraparenchymal major vessel vasospasm in patients with SAH by computed tomographic angiography.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
77
2
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 123 publications
(88 citation statements)
references
References 30 publications
8
77
2
1
Order By: Relevance
“…Previous studies have demonstrated that after aSAH, 30% to 65% of patients will have a cerebral infarct identified on imaging at long-term follow-up. 2,3,8,12,28,29 The rates of early infarcts from previous studies 2,8,12,13 are also comparable with our current data (17% to 34% versus 18%). In contrast to our report, earlier studies were not capable of directly comparing clipping to coiling or determining how different treatment methods may affect infarct rates and neurological outcomes.…”
Section: Discussionsupporting
confidence: 91%
“…Previous studies have demonstrated that after aSAH, 30% to 65% of patients will have a cerebral infarct identified on imaging at long-term follow-up. 2,3,8,12,28,29 The rates of early infarcts from previous studies 2,8,12,13 are also comparable with our current data (17% to 34% versus 18%). In contrast to our report, earlier studies were not capable of directly comparing clipping to coiling or determining how different treatment methods may affect infarct rates and neurological outcomes.…”
Section: Discussionsupporting
confidence: 91%
“…Therefore, there was not a robust association between delayed cerebral ischemia and outcome, but in this study the investigators were not directly examining cerebral infarction. Similar findings were reported in a retrospective review by Shimoda, et al, 52 who found that cerebral infarction was associated with poor outcome but that the relationship of delayed cerebral ischemia to outcome was less obvious. No statistical analysis of these data was performed.…”
Section: Does Cerebral Infarction Cause Poor Outcome?supporting
confidence: 89%
“…Furthermore, not all patients with angiographic vasospasm have symptoms attributable to it, and vice versa. 7,45,52 The term "symptomatic vasospasm" is more subjective, because it depends on how exhaustive the efforts are to exclude other causes of neurological worsening. Furthermore, it is complicated because there may be contributing factors, and because patients with poor-grade SAH are more difficult to assess, particularly if they are sedated.…”
Section: Definitions Of Terminologymentioning
confidence: 99%
See 1 more Smart Citation
“…CT can detect clinically asymptomatic infarcts, particularly in patients with low GCS [69,70]. MRI can detect a larger proportion of asymptomatic infarcts compared to CT [71], and importantly the overall burden of infarcts is correlated with outcome [72,73].…”
Section: Vasospasm After Subarachnoid Hemorrhagementioning
confidence: 99%